A Descriptive Study to Assess the Paternal Knowledge and Attitude towards Exclusive Breastfeeding in a Selected Tertiary Care Setting, Kanchipuram District, Tamil Nadu, India (Medico Legal Update, 2020)
The study aimed at assessing the paternal knowledge and attitude towards exclusive breastfeeding usinga descriptive research design. The sample size consisted of 125 fathers of children in the age group of ?6 months to 2 years of age. A Convenient Sampling was used for selecting the fathers. The demographicprofile of the fathers and infants was assessed through a structured interview. Paternal Knowledge andAttitude towards exclusive breastfeeding was assessed with the help of a self-administered Questionnaireand a self-administered Opinionnaire.The Study findings revealed that nearly 74% of fathers had good knowledge on exclusive breastfeedingand nearly 69% of fathers had positive attitude towards exclusive breastfeeding. Study also revealed apositive correlation (r=0.32) between paternal knowledge and attitude towards exclusive breastfeeding. Astatistically significant association was found between paternal knowledge and paternal age, family type andresidence at p